Does protruding headless cannulated screw reduce fixation stability in tension band wiring technique for patella fractures? a biomechanical study - Mehmet Maden; Omer Berkay Bayraktar; Tayfun Bacaksiz; Ihsan Akan; Bora Uzun; Cemal Kazimoglu (Journal of Orthopaedic Surgery and Research)
Abstract Background The selection of an implant is a critical factor in the surgical treatment of patella fractures due to the risk of various complications, such as non-union, implant failure, and irritation. The present study evaluated and compared the biomechanical strength of headless cannulated screws about screw length using the tension band wiring technique. Methods Forty-eight sawbone patellas with transverse fractures were divided into three fixation groups based on the screw length used in tension band wiring. Overall, three different fixation groups were determined: Group 1 (recessed headless cannulated screw fixation), Group 2 (full-length headless cannulated screw fixation), and Group 3 (protruding headless cannulated screw fixation). A setup was used to simulate a knee with a flexion angle of 60 degrees. Specimens underwent biomechanical testing under axial traction (static test) and cyclic loading (dynamic test). Displacements at 300 Newtons (N), loads at 2 millimetres (mm) displacement, and failure loads were documented for each sample in the static test. In the dynamic test protocol, 10,000 repetitive cycles were performed under physiological load between 100 and 300 N, and final displacements were recorded. Results There were significant differences in the loads achieved at 2 mm displacement levels, and Group 3 demonstrated lower force values compared to other constructs in the static test (P = 0.003). All groups revealed similar displacements at 300 N and failure load values under axial traction. In the dynamic test, Group 3 had significantly higher fracture displacement under cyclic loading compared to the other specimens (P = 0.006). Conclusions This study found headless cannulated screws for transverse patella fracture fixation provide sufficient stability; however, protruding headless screws reduce the fixation strength. Recessed or full-length screws may improve stability and bony healing, potentially preventing complications in patella fractures. Level of evidence Biomechanical study N/A.